Okay. I just need a refresher on this stuff.

6A - 7C = 9

Here's what I'm doing:

6A - 7C + 7C = 9 + 7C

6A = 9 + 7C

A=(9 + 7C)/6

So far so good, right?

Then substituting:

6((9 + 7C)/6) - 7C = 9

Now when I do this I cancel out the "6"'s...maybe that's wrong?

9 + 7C - 7C = 9

7C - 7C = 9 - 9

...okay...I just did some stuff and found that 7C = 9...and that seems to fit... I solved it but...other than just taking a potshot like I did...

How can I go from 7C - 7C = 9 - 9 and get 7C = 9 correctly?

Am I even doing the equation right altogether?

It's been a little while since I've done this math but I wanted to kinda get back up to speed. Thanks in advance for any help!